Six-month immune responses to mRNA-1273 vaccine in combination antiretroviral therapy treated late presenter people with HIV according to previous SARS-CoV-2 infection - Augello, Matteo; Bono, Valeria; Rovito, Roberta; Tincati, Camilla; d'Arminio Monforte, Antonella; Marchetti, Giulia (AIDS (London), 2023)
Immune responses to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) mRNA vaccines in people with HIV (PWH) with a history of late presentation (LP) and their durability have not been fully characterized. In this prospective, longitudinal study, we sought to assess T-cell and humoral responses to SARS-CoV-2 mRNA vaccination up to 6 months in LP-PWH on effective combination antiretroviral therapy (cART) as compared to HIV-negative healthcare workers (HCWs), and to evaluate whether previous SARS-CoV-2 infection modulates immune responses to vaccine. SARS-CoV-2 spike (S)-specific T-cell responses were determined by two complementary flow cytometry methodologies, namely activation-induced marker (AIM) assay and intracellular cytokine staining (ICS), whereas humoral responses were measured by ELISA [anti-receptor binding domain (RBD) antibodies) and receptor-binding inhibition assay (spike-ACE2 binding inhibition activity), before vaccination (T0), 1 month (T1) and 5 months (T2) after the second dose. LP-PWH showed at T1 and T2 significant increase of: S-specific memory and circulating T follicular helper (cTfh) CD4 + T cells; polyfunctional Th1-cytokine (IFN-γ, TNF-α, IL-2)- and Th2-cytokine (IL-4)-producing S-specific CD4 + T cells; anti-RBD antibodies and spike-ACE2 binding inhibition activity. Immune responses to vaccine in LP-PWH were not inferior to HCWs overall, yet S-specific CD8 + T cells and spike-ACE2 binding inhibition activity correlated negatively with markers of immune recovery on cART. Interestingly, natural SARS-CoV-2 infection, while able to sustain S-specific antibody response, seems less efficacious in inducing a T-cell memory and in boosting immune responses to vaccine, possibly reflecting an enduring partial immunodeficiency. Altogether, these findings support the need for additional vaccine doses in PWH with a history of advanced immune depression and poor immune recovery on effective cART.